Control interno en el departamento de ventas de la embotelladora kligma aqua del Cantón Mocache en el año 2022 - Triana García , Zoraida Alexandra (2024)
The main purpose of this investigation entitled “Internal control in the sales department of the Kligma Aqua bottling plant in the Mocache in 2022” was to evaluate the internal control in the sales department; considering that the effective management of internal control becomes an essential element for the success and sustainability of the company in a competitive and constantly changing market. The research is descriptive and field in nature; applying inductive, deductive and descriptive methods, for the purposes of developing the specific objectives of the research, with the support of techniques and instruments that allowed the analysis and processing of key information and documentation, through the observation guide, surveys and interviews carried out. personnel who work in the area under study. Among the main findings, deficiencies in the segregation of functions, lack of clear policies and procedures, and weaknesses in the supervision of daily activities and tasks are revealed. With the results, recommendations were made in order to strengthen the internal control of the water bottling company, ensuring the quality and safety of the products, reliability in compliance with applicable regulations and standards.